Elements of a counter‐exhibition: Excavating and countering a Canadian history and legacy of eugenics. Issue 1 (25th January 2021) - Kelly, Evadne; Manning, Dolleen Tisawii'ashii; Boye, Seika; Rice, Carla; Owen, Dawn; Stonefish, Sky; Stonefish, Mona
Abstract: Into the Light, a recently mounted collectively curated museum exhibition, exposed and countered histories and legacies of 20th‐century "race betterment" pedagogies taught in Ontario's postsecondary institutions that targeted some groups of people, including Anishinaabe, Black, and other racialized populations, and disabled and poor people, with dehumanizing ideas and practices. This article advances understandings of the transformative potential of centralizing marginalized stories in accessible and creative ways to disrupt, counter, and draw critical attention to the brutal impacts of oppressive knowledge. The "counter‐exhibition" prioritized stories of groups unevenly targeted by such oppression to contest and defy singular narratives circulating in institutional knowledge systems of what it means to be human. The authors draw on feminist, decolonial and disability scholarship to analyze the exhibition's curation for the ways it collectively and creatively: (1) brought the past to the present through materializing history and memory in ways that challenged archival silences; and (2) engaged community collaboration using accessible, multisensory, multimedia storytelling to "speak the hard truths of colonialism" (Lonetree) while constructing a new methodology for curating disability and access (Cachia). The authors show how the exhibition used several elements, including counter‐stories, to end legacies of colonial eugenic violence and to proliferate accounts that build solidarity across differences implicated in and impacted by uneven power (Gaztambide‐Fernández).